A screening process for carbonation of vegetable oils using an aluminum(salen) complex with a further application as weldable polymers - Alarcon, Rafael T. [UNESP]; Lamb, Katie J.; Cavalheiro, Éder T. G.; North, Michael; Bannach, Gilbert [UNESP] (Wiley, 2023)
Carbon dioxide (CO2) occurs naturally, though its emissions have been increasing due to anthropogenic activities, and its increasing atmospheric concentration levels are causing a greenhouse effect. In efforts to develop new carbon dioxide utilization (CDU) methodologies, the catalyzed reaction of CO2 with epoxidized vegetable oil, obtained from Brazilian macaw oil and Baru oil, to form carbonated oils for novel and sustainable monomers was explored. A screening process is carried out to develop the best reaction conditions, by varying catalyst/cocatalyst loading, reaction time, CO2 pressure, and the reaction temperature, resulting in conversions of 100%. The aluminum(salen) complex shows a selective and efficient catalyst activity. Both carbonated oils are reacted with amines (1,6-diaminohexane, lysine, and 4,4′-methylenebis [cyclohexylamine]) to provide weldable polyhydroxyurethanes. Polymers synthesized from lysine provide a more selective reaction and higher cross-linked structures, with fewer side reactions involving the glyceride groups. All the synthesized polymers are thermally stable above 200°C and differential scanning calorimetry (DSC) analysis shows two main thermal events, related to the glass transition (Tg) and the topology-freezing transition temperature (Tv). The Tv result indicates that the polymer has weldable properties due to chemical bond exchange. Thus, these polymers can be healed into different shapes upon exposure to red light (660 nm).
Keywords: aluminum catalyst; Brazilian biomass; cyclic carbonate; greenhouse utilization; renewable material; weldable material